Territorial framework of local self-government: basis of legislative regulation - Siryk, Zinoviy; Bilyk, Rostyslav; Panukhnyk, Olena (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
Ukraine is increasingly trying to integrate into European structures. The civilizational, geopolitical and geo-economic choice for our country is obvious, therefore, difficult, consistent and sometimes unconventional and unpopular political decisions are required to implement it. The real implementation of the deconcentration, decentralization and subsidiarity principles in the practice of public administration is necessary, in particular, due to the introduction of new models of relations between the political center and the regions. Regional disproportions in the territory development of Ukraine, the failure to implement the reform on the ground in specific administrative and territorial units, the spread of corruption schemes – all these are the consequences of an ineffective model of local self-government and state management of regional development, that became the beginning of the administrative and territorial reform in the state. And in order to ensure a high-quality process of administrative and territorial reform, it is important, and to some extent and the most basic, is the process of adopting high-quality regulatory base for legislation. The article identifies the main directions for the formation of an effective management system at all levels, including: the formation of an optimal territorial basis, the provision of appropriate material, administrative, organizational and financial conditions for the implementation of the powers granted to them by local governments, a clear delineation of powers between management bodies of different levels based on decentralization, mechanism development of the state control and population involvement in the community development. The legislative base, which was adopted in the context of supporting the reform of local self-government in Ukraine, has been analyzed. The legislative guidelines for the decentralization reform and regional policy in Ukraine have been determined and substantiated. Deficiencies and shortcomings of the normative-legal and institutional support system of the local self-government reform have been identified and ways of their elimination have been proposed.